5G Hairpin and Interdigital Bandpass Filters - Saleh, Sahar; Ismail, Widad; Zainal Abidin, Intan Sorfina; Jamaluddin, Mohd Haizal (International Journal of Integrated Engineering, 2020)
At two low 5G frequency bands: 3.7 GHz - 4.2 GHz and 5.975 GHz -7.125 GHz, Hairpin Bandpass Filter (HPBF) and Interdigital Bandpass Filter (IBF) are designed and simulated in this paper. Both filters show good results in terms of matching and transmission responses with a wide bandwidth through the two frequency bands. HPBF with simple design resulted in good return and insertion losses, < - 10.43 dB and – 0.63 dB, and < - 14.48 dB and –0.46 dB through frequency bands: 3.51 GHz - 4.27 GHz and 5.58 GHz – 7.24 GHz, respectively. In addition to good filter response that IBF provides, it supports high order second harmonics suppression. The simulated S11 and S12 of this filter are < -11.15 dB and –0.63 dB with out of band rejection up to 11.12 GHz through the frequency band 3.56  GHz – 4.25 GHz. Furthermore, at the second frequency band IBF is designed with two different grounding via hole radii (rVia), case 1: rVia = 0.4 mm and case 2: rVia = 0.7 mm. For both cases, the designed filter shows good results with high order second harmonics suppression up to 18.33 GHz and 18.96 GHz. In this paper, High Frequency Structure Simulator (HFSS) software is used to carry out the simulation.